An empirical study on crowdsourcing innovation intermediaries - Silva, Cândida (2022)
Innovation is recognized by academics and practitioners as essential to enhance the competitiveness of organizations and foster their growth. Globalization, the Internet and technologies developments, particu- larly of Web 2.0, and the proliferation of its use by society, have created new forms of communication and interaction between individuals. These individuals become more active in the global network, they stop being mere consumers of information to be also creators. Thus, innovation is increasingly beyond organizational boundaries. The development of Web 2.0, particularly its collaborative component, boost- ed the emergence of crowdsourcing phenomenon. This is essentially a social and organizational phenom- enon in several dimensions. Thus, the main objective of this project was to understand the phenomenon of crowdsourcing for innovation and realize how this can be a path to enhance innovation in organizations. Therefore, it was conducted an empirical study with companies that realize activities of crowdsourcing innovation, open innovation and intermediation of innovation and technology. From this study has emerged a model of knowledge for crowdsourcing innovation intermediaries, which are the main result of this work. The model integrates three components of value capture and creation that an innovation inter- mediary should have to enhance and improve organization innovation capacity: facilitate collaboration between organizations, linking the organization to the external environment, and enabling mediation ser- vices.